IT Solution For Disease Management At PT Panasonic Manufacturing Indonesia - Pardamean, Bens; Djoeang, Anjela Greizaria; Tobing, Nana Rosanna (ComTech: Computer, Mathematics and Engineering Applications, 2010)
One of company’s occupational health programs is disease management which is a part of preventive health care. In its realization, it was discovered that there some challenges in data collection, monitoring of catering and sport activity, employee health reports, and medical costs. The purpose of this study is to design an IT solution for the disease management program at PT. Panasonic Manufacturing Indonesia (PMI). The diseases in focus are diabetes, hypertension, and tuberculosis. Methodology starts with survey on PT. PMI requirements, research parameters, problem analysis, literature study, and system design. Solution is focused on designing a registry system that includes Alert Management System, Food Tracking, EHR, Sport Tracking, Guidelines, and Report System. The results of this study is a web-based information system that can assist health care workers in seeking data, monitoring food intake and sport activity, and reporting systems for upper-level management.